Evaluation of the Reliability of Structural System with Critical Sets Having Joint Elements in Common - Dziubdziela, W.; Kowal, Z. (Engineering Transactions, 1978)
Presented are herein two methods for evaluation the reliability of complex rigid-plastic structural systems, in which occur many minimum critical sets dependent on one another. The first method is based on the Bonferroni's inequality and allows to evaluate both from below and from above the reliability of the system. The second method developed by means of the separation of dependent critical sets is more accurate than the previous one, in particular, for small values of the reliability, however, by this method the evaluation from below is only possible. In the case of large values of the reliability occuring in building structural systems the two evaluations from below are sufficiently accurate.